2022
DOI: 10.1111/cobi.13972
|View full text |Cite
|
Sign up to set email alerts
|

Framing co‐productive conservation in partnership with Arctic Indigenous peoples

Abstract: Indigenous communities at the front lines of climate change and biodiversity loss are increasingly shaping the conservation of lands, waters, and species. The Arctic is a hotbed for emerging local, national, and international conservation efforts, and researchers, managers, and communities alike will benefit from a framework that improves approaches to Indigenous partnerships. Co‐productive conservation is a framework that encompasses both the co‐production of knowledge and the co‐production of public services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…CPF must continue to reflect on the limitations inherent in Western decision-making structures that prevent full consideration of Indigenous Knowledge and laws in transboundary conservation and adaptation, and the ramifications for Blueprint implementation. This critical work can benefit from the growing number of models and resources available for those seeking to unsettle conservation (e.g., Hessami et al 2020;Buschman 2022;Jacobs et al 2022) and climate adaptation (Whyte 2013;Irlbacher-Fox and MacNeill 2020) as well as from the direct guidance and leadership of CPF's own Indigenous partners. The shift to centering Indigenous leadership is predicated on an acknowledgment that Indigenous partner organizations must lead with developing their own approaches to how the steering committee and other CPF partners can support Indigenous priorities.…”
Section: Moving Toward Indigenous Leadershipmentioning
confidence: 99%
“…CPF must continue to reflect on the limitations inherent in Western decision-making structures that prevent full consideration of Indigenous Knowledge and laws in transboundary conservation and adaptation, and the ramifications for Blueprint implementation. This critical work can benefit from the growing number of models and resources available for those seeking to unsettle conservation (e.g., Hessami et al 2020;Buschman 2022;Jacobs et al 2022) and climate adaptation (Whyte 2013;Irlbacher-Fox and MacNeill 2020) as well as from the direct guidance and leadership of CPF's own Indigenous partners. The shift to centering Indigenous leadership is predicated on an acknowledgment that Indigenous partner organizations must lead with developing their own approaches to how the steering committee and other CPF partners can support Indigenous priorities.…”
Section: Moving Toward Indigenous Leadershipmentioning
confidence: 99%
“…The culture of science is as varied and unstable as any human culture (Knorr‐Cetina, 1999; Latour & Woolgar, 2013; Ottinger & Cohen, 2012; Traweek, 1988). Likewise, much valuable knowledge (especially with regard to conservation) is produced by those who may not be recognized as scientists (Buschman, 2022; Hernandez, 2022; Parthasarathy, 2011; Wynne, 1998). Yet, historically much work has gone into delineating the borders of science and—albeit futilely—attempting to isolate it from politics and practical concern (Brown, 2015; Gieryn, 1995; Stokes, 1997).…”
Section: The Logic Of Inquiry Versus the Logic Of Actionmentioning
confidence: 99%
“…While western scientific knowledge (WSK) offers a great deal to help prevent and adapt to climate change and associated water challenges, the need is greater than what WSK can provide on its own. , Indigenous knowledge (IK; also known as traditional knowledge, Indigenous science, and by specific terms such as Inuit Qaujimajatuqangit), primarily valuable in its own right, is also a powerful resource through its holistic worldview (that includes but is not limited to entire social/environmental/water systems), embracing complexity and great depth in time. , The deep-rooted connection of IK to its social and environmental context has encouraged various efforts to connect IK and WSK to address real-world challenges such as climate change. In seeking to do so in recent studies on climate-driven changes to water quality in Alaska, we have found the experiences of scholars and practitioners working with IK and WSK , to be invaluable in our planning for IK–WSK convergence for understanding and solving water-related challenges throughout all stages of a convergence project . Here, primarily for the benefit of non-Indigenous academic researchers unfamiliar with convergence research, we present these ideas as a contribution to the continuing conversation about respectful and equitable partnerships involving IK and WSK to address urgent, complex problems such as climate change.…”
Section: Introductionmentioning
confidence: 99%